Effect of Moringa oleifera Based Total Mixed Ration on Parasite Infestation in Meat Goats - Muhammad Adib Othman (2019)
Feed cost for meat goats in Malaysia is very high due to the imported concentrates. Hence, the farmers feed their animals with forage solely such as Napier grass. Napier grass has low nutritional value, thus the growth of the animal and production are not good due to the inappropriate and low nutrition feed. Legumes is a very good source of dietary protein for animals. Nutritionally, legumes also tend to have higher levels of energy per unit weight and more calcium than grasses. Therefore, the purpose of this study was to evaluate the effect of Moringa Oleifera based total mixed ration (mTMR) on parasite infestation in meat goats and to compare the effectiveness of mTMR with basal diet. A total of six animals were used and divided into two groups, three for control and three for treatment, they were grouped based on the average weight which is 30kg. Two different groups of treatments (control and mTMR) were used. Fecal egg count was done to evaluate the egg per gram (EPG) of nematode eggs in gastrointestinal tract of the goats. The mMTR is more effective, efficient and profitable to feed the animals. From this research the result showed that the mean EPG of the parasite infestation between control group and mTMR group had no significant difference. However, the Moringa Oleifera based total mixed ration was a good diet for better health condition and reduce the EPG in the gastrointestinal tract of the goats.